Analisis Kinerja Keuangan Koperasi Unit Desa Langgeng Desa Inauga Kecamatan Mimika Baru Kabupaten Mimika - Gobai, Anton; Tumbel, Tinneke M.; Keles, Dantje (Sam Ratulangi University, 2019)
This study aims to determine the structure of KUD in terms of liquidity, solvency, and profitability. While the benefits that the author can provide to the cooperative are as a matter of consideration for KUD leaders to take policies as meeting the capital requirements of the KUD. how much influence the short-term and long-term debt on cooperative solvency in accordance with the problems stated and supported by a review of the literature on capital, capital structure and type of ratio analysis that the authors take this conclusion is not the achievement of solvency ratios due to increased fund and cost profitability collection methods used in this study are interviews (data collection with direct interviews with parties related to the data needed) and (cooperative financial statements). In analyzing the data the writer uses descriptive analysis method. Based on the results of this study there are those that cause the current to fluctuate ratio from year to year some of the working capital invested in the ratio is not smooth. Judging from the cash ratio it is also known that the condition of cooperative liquidity is still low due to the lack of effective cooperative spending policies, increasing the solvency ratio of cooperatives from year to year caused by an increase in the role of own capital compared to foreign capital. While an increase in profitability ratios is caused by an increase in profits achieved by cooperatives, this means that cooperatives have been efficient in their use.